2017
DOI: 10.1177/0278364917722396
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale cost function learning for path planning using deep inverse reinforcement learning

Abstract: We present an approach for learning spatial traversability maps for driving in complex, urban environments based on an extensive dataset demonstrating the driving behaviour of human experts. The direct end-to-end mapping from raw input data to cost bypasses the effort of manually designing parts of the pipeline, exploits a large number of data samples, and can be framed additionally to refine handcrafted cost maps produced based on manual hand-engineered features. To achieve this, we introduce a maximum-entrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(99 citation statements)
references
References 25 publications
0
99
0
Order By: Relevance
“…Additionally, thanks to convolutional operators, they are able to capture spatial correlations in the data. Wulfmeier et al (123) were able to learn an end-to-end mapping from raw input data to cost map from more than 25,000 demonstrations over 120 km of driving. Lastly, Kuefler et al (124) demonstrated the effectiveness of generative adversarial imitation learning (125), extended to the optimization of recurrent policies.…”
Section: Wwwannualreviewsorg • Decision-making For Autonomousmentioning
confidence: 99%
“…Additionally, thanks to convolutional operators, they are able to capture spatial correlations in the data. Wulfmeier et al (123) were able to learn an end-to-end mapping from raw input data to cost map from more than 25,000 demonstrations over 120 km of driving. Lastly, Kuefler et al (124) demonstrated the effectiveness of generative adversarial imitation learning (125), extended to the optimization of recurrent policies.…”
Section: Wwwannualreviewsorg • Decision-making For Autonomousmentioning
confidence: 99%
“…The system was shown to learn drivers' personal driving styles from minimal training data and performed adequately in simulated testing. Building on the IRL approaches, Wulfmeier et al [133] proposed an IRL approach for deep learning. The proposed algorithm is based on the Maximum Entropy [134] model for a trajectory planner, and uses CNNs to infer the reward functions from expert demonstration.…”
Section: Simultaneous Lateral and Longitudinal Control Systemsmentioning
confidence: 99%
“…The proposed method is demonstrated on a task of learning driver route choices where the demonstrations may be suboptimal and non-deterministic. This approach is extended to a deep-learning framework in [Wulfmeier et al 2015]. Maximum entropy objective functions enable straightforward learning of the network weights, and thus the use of deep networks trained with stochastic gradient descent [Wulfmeier et al 2015].…”
Section: Apprenticeship Learningmentioning
confidence: 99%
“…This approach is extended to a deep-learning framework in [Wulfmeier et al 2015]. Maximum entropy objective functions enable straightforward learning of the network weights, and thus the use of deep networks trained with stochastic gradient descent [Wulfmeier et al 2015]. The deep architecture is further extended to learn the features via Convolution layers instead of using pre-extracted features.…”
Section: Apprenticeship Learningmentioning
confidence: 99%